Determination of Variables Influencing the Quality of Life in Children with Liver Transplantation - Nursen Altuğ; Çiğdem Omur Ecevit; Miray Karakoyun; Ezgi Kıran Taşçı; Bahire Bolışık; Sema Aydoğdu (Galenos Yayinevi, 2019)
Aim:This clinical study examined various dimensions of the Quality of Life (QoL) in children who had undergone liver transplantation.Materials and Methods:The patient group (n=50) of the study consisted of children and their families where the child had received a liver transplant (possibly from their mother) in Ege University Organ Transplant Research Center. The control group (n=50) consisted of children and their families who did not undergo any organ transplants, did not have any health issues and were of similar age, gender and socio-economic status with the members of the study group. The children in the study were examined with a QoL questionnaire named KINDer Lebensqualitätsfragebogen (Children's Quality of Life Questionnaire).Results:The overall QoL and the QoL in the physical, emotional, self-esteem, family, friend, and school sub-categories as reported by the children themselves in the study group, in both the 8-12 and 13-16 year age groups were determined to be higher (p<0.05) when compared to those children in the control group. Similarly, the QoL for the children in the study group, as reported by their families were determined to be higher (p<0.05) when compared to the control group.Conclusion:Liver transplantation has effects on the QoL of both the children and their families.